TELAAH KEBERAGAMAAN RADIKALISME ISLAM DAN AKTUALISASINYA DALAM PENDIDIKAN - Sufyan Ats-Tsauri; Mahmud Arif (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Radicalisme is an issue that is no longer new to the dynamics of indonesian society. Even so, is thete are many issue that can lead to radicalism. However, it is religious issue that often becomes targets that become the backround for the emergence of friction of understanding that often lead to radical action. In the context of radicalism is an issue that is familiar to the Islamic world because so many acts of radicalism in the historical record. This paper aims to explain the diversity of radicalism in Islam and its actualization in education. This research uses library research that is data sourced from various scientific papers such as: books, thesis, desertation, journals and several other types of ilmiyah writings as a source of data for analysis of its content (conten analisys). This study explains radicalism and its flow. In indonesia radicalism has four traditions of wahabi, salafi, jihadi and Takfiri groups of the four groups that use violent movements and caci makian is a jihadi movement, this movement prohibits killing non-Muslims and the takfiri group is the most extremist of radical movements because this group encourages all infidels except those in the group. This group is often troubling the community so that the implications go into the world of education. The phenomenon of fact occurs in fernanando network which is an alumnus of UIN syarif Jakarta. And the doctrine in this radicalism movement is often included in the order of public college education so that this movement often occurs when it feels an unfairness in the campus world so that it is moved to make a radical movement.